The Correlation Between Learning Achievement and The Level of Presence and The Intensity Attention in Following Lectures - Syarfi, M. (Journal of Educational Sciences, 2022)
The on time presence of attending classroom meeting with lectures is one of the factors mostly associated with the learning achievements of students. To find out the possibility of a correlation between the two variables certainly requires scientific, in-depth and measurable studies. The population of this study is all students of the English Study Program FKIP Riau University, whose samples were taken by using quota purposive sampling technique, namely by providing them assessment of samples among the selected population (Campbell. S. et.al. 2020). This technique was used under the consideration of the limited time, energy and funds the researcher had. Quota was used to determine the number of samples, while purposive was intended to determine the subject matters whose presentation might be in the forms lectures, discussions and assignments. Randomization technique was used to determine the individuals included in involved as the subject of the study. The collected data, especially those obtained through questionnaires, were analyzed and given scores. The scores were then analyzed using a statistical analysis of abc design variance. Meanwhile, data concerning student achievement used a single or univariate change analysis with the intention of testing assumptions by using variance analysis. The results of the data analysis indicate that (1) there was no significant correlation between the learning achievement and the level of participation and the intensity of attention following the learning or lecture process (2) there was no significant correlation between students attendant rate and learning achievement.